(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
Messapian is the pre-Roman fragmentary language of the 2nd Augustan region Apulia et Calabria, attested between the 6th and the 2nd c. BC. Almost 650 inscriptions, mostly personal names, are known from this region. The linguistic position of the language within the Indo-Europen language is still debated, as it seems to be isolated in the framework of the languages known in ancient Italy. The author offers an overview of pre-Roman Apulia as described by ancient authors, focussing on the definition of the term ‘Messapic’. She further describes the epigraphic and linguistic features, with in-depth considerations on the Messapic palatalisation and on the -ihi genitive, topics which still raise discussion among the specialists.